Echoes of Deception: A Chronicle of Unusual Ventricular Pseudoaneurysm- A Case Series - Munesh Kumar; Arzoo Kadian; Vijay Sharma; S.K. Tandon; Mohit Gupta (International Journal of Medical Toxicology and Legal Medicine, 2025)
Background: Infective endocarditis (IE) is an infection involving the heart valves or the endocardial surface, typically resulting from bacteraemia. It can lead to serious complications, including perforation of the valve leaflets, annular abscesses, formation of fistulous tracts, and destruction of adjacent cardiac structures such as the subaortic region.1,2 Case Presentation: This case series illustrates an atypical and fatal complication of IE, which is left ventricular pseudoaneurysm (LVPA), an uncommon cardiac lesion that can be overlooked during life and often identified during postmortem examination due to its asymptomatic progression.3,4 We present two cases of left ventricular pseudoaneurysms associated with fibrotic valvular vegetations and myocardial damage consistent with previously unrecognized infective endocarditis in apparently healthy males, revealed during the medicolegal autopsy. Conclusion: These findings highlight the silent but deadly course of LVPA secondary to IE and emphasize the importance of vigilance in at-risk patients. Timely imaging and surgical management may prevent catastrophic rupture.4,5 Autopsy remains vital in uncovering such silent, fatal complications.6 We also suggest implications for public health and clinical awareness.